Overexpression of the Drosophila vesicular monoamine transporter increases motor activity and courtship but decreases the behavioral response to cocaine. - Chang, H.Y.; Grygoruk, A.; Brooks, E.S.; Ackerson, L.C.; Maidment, N.T.; Bainton, R.J.; Krantz, D.E. (Molecular Psychiatry, 2006)
Aminergic signaling pathways have been implicated in a variety of neuropsychiatric illnesses, but the mechanisms by which these pathways influence complex behavior remain obscure. Vesicular monoamine transporters (VMATs) have been shown to regulate the amount of monoamine neurotransmitter that is stored and released from synaptic vesicles in mammalian systems, and an increase in their expression has been observed in bipolar patients. The model organism Drosophila melanogaster provides a powerful, but underutilized genetic system for studying how dopamine (DA) and serotonin (5HT) may influence behavior. We show that a Drosophila isoform of VMAT (DVMAT-A) is expressed in both dopaminergic and serotonergic neurons in the adult Drosophila brain. Overexpression of DVMAT-A in these cells potentiates stereotypic grooming behaviors and locomotion and can be reversed by reserpine, which blocks DVMAT activity, and haloperidol, a DA receptor antagonist. We also observe a prolongation of courtship behavior, a decrease in successful mating and a decrease in fertility, suggesting a role for aminergic circuits in the modulation of sexual behaviors. Finally, we find that DMVAT-A overexpression decreases the fly's sensitivity to cocaine, suggesting that the synaptic machinery responsible for this behavior may be downregulated. DVMAT transgenes may be targeted to additional neuronal pathways using standard Drosophila techniques, and our results provide a novel paradigm to study the mechanisms by which monoamines regulate complex behaviors relevant to neuropsychiatric illness.